Determinants of Carbon Emission Disclosure in Palm Oil Industries - Wike Pratiwi; Muhammad Yazid Bustomi; Wardatul Hidayah (Jurnal Loupe, 2024)
The acceleration of climate change is greatly influenced by carbon emissions from industrial processes, particularly those that come into direct touch with natural resources. One industry that interacts directly with natural resources is the palm oil sector. From clearing land to managing oil palm plantations, manufacturing palm oil FFB, and distributing palm oil goods, all of this industrial business activity generates carbon emissions that have the potential to harm the environment. The purpose of this study is to investigate the low level of transparency and reporting of carbon activities. A number of variables, such as profitability, firm size, environmental performance, managerial ownership, and corporate worth, are used in this study to analyse carbon emission disclosure. This research is a type of quantitative research using secondary data, namely 25 samples of the palm oil industry in Indonesia for the period 2021–2023. The research results show that profitability and managerial ownership company size have insignificant results on Carbon Emission Disclosure, while environmental performance has a significant effect on Carbon Emission Disclosure. The Carbon Emission Disclosure hypothesis on company value also shows significant results where the more a business entity discloses and reports its carbon activities, the more investor confidence it has which can be seen in the high share value.